Continuity of Midwifery Care with the Implementation of Prenatal Yoga and Health Education: A Case Study at Garuda Public Health Center, Bandung City - Rahayu, Eka Fuji; Ferina , Ferina; Sriwenda , Djudju (CV. Tripe Konsultan, 2026)
Continuity of midwifery care represents a holistic and woman-centered service model that ensures comprehensive support throughout pregnancy, childbirth, postpartum, neonatal care, and family planning. One of the most common discomforts experienced by pregnant women in the third trimester is low back pain and psychological anxiety prior to labor. Prenatal yoga has emerged as a safe, non-pharmacological intervention that integrates physical movement, breathing techniques, and relaxation to alleviate such discomforts. This educational article aims to examine the integration of prenatal yoga within the continuity of midwifery care framework as an effective learning-based intervention in maternal health services. Using a descriptive-analytical approach derived from a comprehensive midwifery care case study conducted at a primary healthcare center, this article highlights the clinical, educational, and experiential benefits of prenatal yoga in improving maternal comfort, psychological readiness, and childbirth outcomes. The findings demonstrate that prenatal yoga contributes positively to maternal well-being, supports normal labor processes, and enhances the quality of midwifery education and practice.